The Construction of Abdurrahman Wahid’s Image in the Lyrics of “GusDur Pendekar Rakyat”: A Critical Discourse Analysis - Hayiz Historia Adhi Pratama; Achmad Kanzulfikar; Lisy Tantowi (Jurnal Mutakallimin : Jurnal Ilmu Komunikasi, 2026)
The song Gus Dur Pendekar Rakyat portrays the socio-political conditions during the leadership of Abdurrahman Wahid, who carried out reform efforts amid the lingering influence of the New Order regime. Gus Dur presidency was marked by challenges related to potential disintegration and the resistance of New Order sympathizers. Eventually, he was removed from office following the MPR. This study focuses on the construction of Gus Dur’s public image as represented in the song Gus Dur Pendekar Rakyat. Employing a qualitative approach with Fairclough Critical Discourse Analysis method, the research explores how the lyrics build a particular representation of Gus Dur. The findings indicate that the song constructs Gus Dur as a leader who embodies simplicity in governing. His leadership style, reflected in his policies, positioned him as a political target for New Order sympathizers. Nevertheless, his policies were oriented toward the public interest, which contributed to his widespread admiration among the people. Furthermore, the study finds that the use of YouTube and TikTok as dissemination platforms has strengthened public recognition of Gus Dur—not only as an Islamic scholar, former president, and national hero, but also as a figure closely associated with the socio-political dynamics of his era.